Implementation Of Business Strategies In Facing Coffee Industry Competition (Case Study of PT. Ulubelu Cofco Abadi - Michaellim Michaellim; Habiburahman Habiburahman (International Journal of Economics, Business and Innovation Research, 2024)
Ulubelu Cofco Abadi is one of them business coffee home industry in Bandar Lampung. The problems faced by PT. Ulubelu Cofco Abadi , namely PT Sales . Ulubelu Cofco Perpetual fluctuates . This research aims to find out what business strategies should be used to obtain a market leader position for PT. Ulubelu Cofco Abadi. The method used in This research is a qualitative analysis method, using the SWOT analysis tool ( strength , weakness, opportunity and threat) Judging from the Cartesian SWOT diagram where PT. Ulubelu Cofco Abadi is in quadrant 1, namely: strategy cost leadership ( reducing total costs , determining the right cost price), strategy differentiation (adding new products, food or drinks), focus strategy ( maintaining product quality , cleanliness is always maintained, more friendly service to consumers ) .